The Degree of Faculty Practice of Educational Change Management Strategies at Some Faculties of Zintan University (Al-Jabal Journal of Humanities and Applied Sciences, 2024)
The study aims to evaluate the extent of use by faculty members in some colleges of Zintan University of educational change management strategies. It focused on two main axes: the first related to organizational culture and technology and their impact on the faculty members' abilities to adopt educational change management strategies, while the second pertains to the behavioral aspect, measuring the awareness and perception of faculty members in applying these strategies The researcher followed the presentation of results as follows:-Description of the sample characteristics, including gender, age, position, academic qualification, specialization, and years of experience.-Presentation of the results of the sample individuals' consensus on the previously mentioned axes.-Testing the study hypotheses (first and second) using a descriptive analytical approach and utilizing a questionnaire as a data collection tool. It was distributed to a sample of 60 individuals out of a total study population of 170 faculty members in some colleges of Zintan University. The researcher retrieved 50 completed questionnaires, representing 90% of the distributed surveys.  The study concluded that the faculty members' practice level of educational change management strategies in some colleges of Zintan University was moderate, indicating opportunities for improvement and development in utilizing strategies related to educational change management in the academic environment of these colleges.
Keywords: Educational Change Management Strategies, Organizational Culture, Practice Level, Faculty Members' Awareness and Perception